2009
DOI: 10.1007/s11671-009-9334-6
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the In Vivo Toxicity of Gold Nanoparticles

Abstract: The environmental impact of nanoparticles is evident; however, their toxicity due to their nanosize is rarely discussed. Gold nanoparticles (GNPs) may serve as a promising model to address the size-dependent biological response to nanoparticles because they show good biocompatibility and their size can be controlled with great precision during their chemical synthesis. Naked GNPs ranging from 3 to 100 nm were injected intraperitoneally into BALB/C mice at a dose of 8 mg/kg/week. GNPs of 3, 5, 50, and 100 nm di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
442
2
7

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 600 publications
(467 citation statements)
references
References 25 publications
(22 reference statements)
16
442
2
7
Order By: Relevance
“…Similar results were obtained for 3 nm AuNPs, 5nm, 5, 12, 20, 30, 50, and 70nm, 3, 5, 8, 12, 17, 37, 50, and 1200nm, 4 and 13nm, and 40nm 112 [53][54][55][56][57][58]. Taking into account the abovementioned data, it could be possible to expand the boundaries to both the lower level (to 3 nm) and larger particles up to 100 nm to avoid a toxic AuNP effect, if we are considering a limited dose of about 10 12 particles/ml.…”
Section: Particle Size Effectsupporting
confidence: 86%
“…Similar results were obtained for 3 nm AuNPs, 5nm, 5, 12, 20, 30, 50, and 70nm, 3, 5, 8, 12, 17, 37, 50, and 1200nm, 4 and 13nm, and 40nm 112 [53][54][55][56][57][58]. Taking into account the abovementioned data, it could be possible to expand the boundaries to both the lower level (to 3 nm) and larger particles up to 100 nm to avoid a toxic AuNP effect, if we are considering a limited dose of about 10 12 particles/ml.…”
Section: Particle Size Effectsupporting
confidence: 86%
“…Although both the in vivo and in vitro testing of AuNPs of different sizes are known to sometimes produce contradictory results 17,18 , we first focused on the 35 nm AuNPs as an example for microscopic detection since this size is easier to examine. Our method was based on correlating the signals of the transmitted high energy electrons and the scattered low energy ones coming mainly from the surface.…”
Section: Resultsmentioning
confidence: 99%
“…In the literature, AuNPs have been reported to lack the ability to induce adverse and acute toxicity [17] and are thus deemed to be biocompatible entities for use in biomedical applications [17,18] . However, recent studies have shown that there could be more to AuNP toxicity than already surmised and that the extent of toxicity response is closely associated with the size of the AuNPs [19,20] . Investigations have revealed that decreasing the size of NPs correlated with more widespread tissue distribution, heightened potential to deeper penetration within certain tissues, more effective internalization by cells, and increased toxic effects [21] .…”
Section: Aunps and Cytotoxicitymentioning
confidence: 99%